Bringing Hetero‐Polyacid‐Based Underwater Adhesive as Printable Cathode Coating for Self‐Powered Electrochromic Aqueous Batteries. (23rd April 2018) - Li, Xiaodong; Du, Zhanglei; Song, Zhengyi; Li, Bao; Wu, Lixin; Liu, Qingping; Zhang, Houyu; Li, Wen
Abstract: The advent of electrochromic aqueous batteries represents a promising trend in the development of smart and environmentally friendly energy storage devices. However, it remains a great challenge to integrate electrochromic, flexible, and patterned features into a single battery unit through a simple operation. Herein, an entirely new class of hetero‐polyacid‐based underwater adhesives is designed and synthesized by combining the redox properties of hetero‐polyacids and the water‐resistant binding of adhesives in single system. The hybrid underwater adhesives not only serve as printable electrode coatings in aqueous solution but also offer unique electrochromic feature for guiding the convenient fabrication of self‐powered electrochromic aqueous battery. The reversible discharging and H2 O2 assistant charging behavior is also demonstrated. This kind of wet and electrochromic adhesive with excellent toleration of mechanical deformation offers great promise in developing flexible and smart energy storage configuration, which provides a user‐device interface platform allowing one to evaluate the battery's charging state based on the naked eye–visible change in color. Abstract : Printable electrochromic adhesives are fabricated through co‐assembly of hetero‐polyacid and aromatic amino acids in water. The resultant patterned electrode coatings exhibit excellent bending and stretching tolerance in aqueous solution, and thus open up new opportunities for creating flexible and smart batteries, where the discharging and charging states can be monitored by changes in color visible to the naked eye.